Five new species of Myrsidea Waterston (Phthiraptera: Menoponidae) from saltators and grosbeaks (Passeriformes: Cardinalidae) - Price, Roger D.; Johnson, Kevin P.; Dalgleish, Robert C. (Zootaxa, 2008)
Five new species of Myrsidea parasitic on members of the avian family Cardinalidae are described. They and their type hosts are M. lightae ex the Buff-throated Saltator, Saltator maximus (Statius Müller, 1776), M. markhafneri ex the Slatecolored Grosbeak, S. grossus (Linnaeus, 1766), M. pittendrighi ex the Streaked Saltator, S. striatipectus Lafresnaye, 1847, and M. johnklickai and M.sychrai ex the Blue-black Grosbeak, Cyanocompsa cyanoides (Lafresnaye, 1847). Results from sequences of a portion of the mitochondrial COI gene for several specimens of two of these species and other species of Myrsidea are presented.